Improving EFL Students’ Listening and Critical Thinking Skills through Higher-Order Thinking Questions - Ramadhana, Diba; Firdaus, Iqbal (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2025)
This study explores the effectiveness of higher-order thinking skills (HOTS) questions in fostering critical thinking among EFL learners in a Listening for Academic Purposes (LAP) class. While academic listening inherently involves cognitive processes such as inference, evaluation, and analysis, EFL instruction often focuses on lower-order comprehension tasks. To address this gap, the study implements HOTS-based questioning strategies within a Classroom Action Research (CAR) framework, promoting reflective teaching and continuous improvement. The research was conducted with six intermediate EFL students over two cycles, incorporating academic audio materials, structured HOTS questions, and student-centered discussions. Data were collected through observation checklists, student reflection sheets, and pre- and post-tests. Findings indicate that students initially struggled with higher-order questions but showed significant improvement in both critical thinking and listening performance after receiving appropriate scaffolding and practice. The post-test results and classroom observations revealed increased engagement, deeper analysis, and more thoughtful responses. This study concludes that integrating HOTS questions into LAP instruction can effectively enhance critical thinking skills in EFL learners. It also highlights the value of reflective teaching practices in adapting instructional strategies to meet learner needs. Implications are offered for language teachers, curriculum designers, and future researchers aiming to enrich listening pedagogy through critical thinking development.